The Tale of Tessie the Textile Worker: Female Textile Workers in Cornwall During World War II - Scheinberg, Ellen (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1994)
The recent historiography pertaining to women during World War II hast ended to focus on women in either the war industries or armed forces. While the first feminist scholars argued that women experienced a type of second emancipation during this period due to changes in societal attitudes, more recently, historians have contended that women were temporarily treated to certain economic and social benefits during the War because the government and industries were in desperate need of workers. This paper attempts to offer an alternative interpretation of women's experiences during this time, through the investigation of female textile workers in Cornwall, Ontario. Using a dual structural analysis, this study illustrates how male union leaders and company owners often collaborated in maintaining a segregated work force. Instead of experiencing a type of liberation from traditional occupational constraints, Cornwall's female textile workers remained subjugated in lower paying and lower skilled "female" jobs in the mills. Within this industry then, continuity rather than change characterized the experiences of female textile workers during World War II.